3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland (University of Jyväskylä; University of Salzburg, 2015)
The 3rd International Congress on Science and Nordic Skiing will be organized by the Sports Technology Unit (Vuokatti) of the Department of Biology of Physical Activity, University of Jyväskylä, Finland, together with the Department of Sport Science and Kinesiology, University of Salzburg, Austria and with Vuokatti Sports Institute, The Centre for Measurement and Information Systems (CEMIS) and Municipality of Sotkamo. The program consisted of 15 invited presentations, 30 oral, 10 poster presentations, panel discussion and laboratory demonstrations, overall representing 12 different countries. The Congress program consisted of familiar topics such as biomechanics, physiology, biathlon, ski jumping and technology. In addition, Paralympic Sport in Nordic Skiing, Snowboarding as well as an exciting Young Investigator Award competition had their own sessions In this book the proceedings of this Congress are presented (abstracts).